A Case of Atypical Hemolytic Uremic Syndrome (Iranian Journal of Kidney Diseases, 2014)
A 9-year-old boy presented with fever not responding to antibiotic therapy and elevated blood urea and serum creatinine levels. The patient developed microangiopathic hemolytic anemia and thrombocytopenia during the hospital stay. Kidney biopsy confirmed the diagnosis of atypical hemolytic uremic syndrome (HUS). The patient had sufficient urine output, normal blood pressure, and no evidence of peripheral edema during the whole course of his disease. Serum levels of anti-Epstein-Barr virus immunoglobulin M was elevated, indicating the possible role of Epstein-Barr virus infection in inducing atypical HUS in this patient. The patient underwent hemodialysis with dramatic response. He was discharged with normal kidney function after a few days. Kidney function and platelet count were normal 12 months after the initial presentation. This case report shows that atypical hemolytic uremic syndrome could have unusual presentations such as the absence of oliguria, hypertension, and edema, with rapid recovery and good prognosis.